Physiological consequences of the P2328S mutation in the ryanodine receptor (RyR2) gene in genetically modified murine hearts - Goddard, C A (Blackwell Publishing Ltd, 2008)
AIM: To explore the physiological consequences of the ryanodine receptor (RyR2)-P2328S mutation associated with catecholaminergic polymorphic ventricular tachycardia (CPVT). METHODS: We generated heterozygotic (RyR2(p/s)) and homozygotic (RyR2(s/s)) transgenic mice and studied Ca(2+) signals from regularly stimulated, Fluo-3-loaded, cardiac myocytes. Results were compared with monophasic action potentials (MAPs) in Langendorff-perfused hearts under both regular and programmed electrical stimulation (PES). RESULTS: Evoked Ca(2+) transients from wild-type (WT), heterozygote (RyR2(p/s)) and homozygote (RyR2(s/s)) myocytes had indistinguishable peak amplitudes with RyR2(s/s) showing subsidiary events. Adding 100 nm isoproterenol produced both ectopic peaks and subsidiary events in WT but not RyR2(p/s) and ectopic peaks and reduced amplitudes of evoked peaks in RyR2(s/s). Regularly stimulated WT, RyR2(p/s) and RyR2(s/s) hearts showed indistinguishable MAP durations and refractory periods. RyR2(p/s) hearts showed non-sustained ventricular tachycardias (nsVTs) only with PES. Both nsVTs and sustained VTs (sVTs) occurred with regular stimuli and PES with isoproterenol treatment. RyR2(s/s) hearts showed higher incidences of nsVTs before but mainly sVTs after introduction of isoproterenol with both regular stimuli and PES, particularly at higher pacing frequencies. Additionally, intrinsically beating RyR2(s/s) showed extrasystolic events often followed by spontaneous sVT. CONCLUSION: The RyR2-P2328S mutation results in marked alterations in cellular Ca(2+) homeostasis and arrhythmogenic properties resembling CPVT with greater effects in the homozygote than the heterozygote demonstrating an important gene dosage effect.